Long live the host!: proteomic analysis reveals possible strategies for parasitic manipulation of its social host - Hartke, Juliane; Ceron-Noriega, Alejandro; Stoldt, Marah; Sistermans, Tom; Kever, Marion; Fuchs, Jenny; Butter, Falk; Foitzik, Susanne (Molecular ecology, 2023)
Parasites with complex life cycles often manipulate the phenotype of their intermediate hosts to increase the probability of transmission to their definitive hosts. Infection with Anomotaenia brevis, a cestode that uses Temnothorax nylanderi ants as intermediate hosts, leads to a multiple-fold extension of host lifespan and to changes in behaviour, morphology and colouration. The mechanisms behind these changes are unknown, as is whether the increased longevity is achieved through parasite manipulation. Here, we demonstrate that the parasite releases proteins into its host with functions that might explain the observed changes. These parasitic proteins make up a substantial portion of the proteome of the hosts' haemolymph, and thioredoxin peroxidase and superoxide dismutase, two antioxidants, exhibited the highest abundances among them. The largest part of the secreted proteins could not be annotated, indicating they are either novel or severely altered during recent coevolution to function in host manipulation. We also detected shifts in the hosts' proteome with infection, in particular an overabundance of vitellogenin-like A in infected ants, a protein that regulates division of labour in Temnothorax ants, which could explain the observed behavioural changes. Our results thus suggest two different strategies that might be employed by this parasite to manipulate its host: secreting proteins with immediate influence on the host's phenotype and altering the host's translational activity. Our findings highlight the intricate molecular interplay required to influence the phenotype of a host and point to potential signalling pathways and genes involved in parasite-host communication.
Online verfügbar: 5. Oktober 2023
Gesehen am 23.01.2024